Corporate Social Responsibility(CSR) Evaluation & Effectiveness of Disclosure and its Impact on Financial Performance: A Case of Indonesian Corporations by Longitudinal Evidence - Muhammad Asif Khan; Adler Haymans Manurung (Penerbit Goodwood, 2022)
Purpose: To see if corporate social responsibility (CSR) is linked to financial performance in Indonesian enterprises. Despite the fact that CSR was first revealed in Indonesia. Method:This study, which is based on a longitudinal information study, consists of the two hundred most famous organizations, which were chosen from 672 recorded corporations that lead Bursa Indonesia between 2010 and 2020 by content Analysis. Secondary data analysis of recorded market data from Indonesia was used in this study. The necessary information was retrieved and recorded so that it could be analyzed subsequently. Additionally, SPSS was used to analyze the filtered data from which a generalized linear regression model was adopted. Result: The linearity test reveals a linear link between Corporate Social Responsibility and Firm Performance. Leverage, income per share, firm size, resource turnover, and corporate social responsibility have all been identified as critical indicators of an organization's financial performance in past studies. The present results corroborate this. Limitation: Expanding the specimen estimate, possibly to different agencies not fundamentally recorded; probably to 250 best organizations in Indonesia may consider a preferred measure of the impact that CSR has on the financial performance of Indonesian agencies. Contributions: Through its observations and discussions, this research contributes to theoretical and methodological advancements in the field of business. The report reinforces and advises businesses on the importance of corporate responsibility in their quest to increase financial performance, particularly in Indonesia. If enterprises follow the study's recommendations, they can achieve unprecedented levels of financial enactment.